Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To analyze how the zero of the parent function \( y = x^4 \) is affected by the transformation to \( y = (x + 4)^4 \), let's first identify the zero of the parent function and understand the transformation applied.
1. Identifying the Zero of the Parent Function:
The parent function is \( y = x^4 \). To find the zero of this function, we set \( y = 0 \):
[tex]\[ x^4 = 0 \][/tex]
Solving for \( x \), we get:
[tex]\[ x = 0 \][/tex]
Hence, the zero of the function \( y = x^4 \) is at \( x = 0 \).
2. Understanding the Transformation:
The given transformed function is \( y = (x + 4)^4 \). This transformation involves \( (x + 4) \). When we add a constant inside the function, it results in a horizontal shift. Specifically, adding a positive constant \( +4 \) inside the parentheses shifts the graph to the left by that number of units.
3. Determining the New Zero:
To find the new zero, we set the transformed function to zero and solve for \( x \):
[tex]\[ (x + 4)^4 = 0 \][/tex]
Solving for \( x \), we get:
[tex]\[ x + 4 = 0 \][/tex]
[tex]\[ x = -4 \][/tex]
Therefore, the zero of the transformed function \( y = (x + 4)^4 \) is at \( x = -4 \).
4. Comparing the Zero of the Parent and Transformed Functions:
- The original zero was at \( x = 0 \).
- The new zero is at \( x = -4 \), which means the zero has been shifted 4 units to the left from the original position.
Therefore, the correct answer is:
C. The zero of the function is shifted 4 units to the left.
1. Identifying the Zero of the Parent Function:
The parent function is \( y = x^4 \). To find the zero of this function, we set \( y = 0 \):
[tex]\[ x^4 = 0 \][/tex]
Solving for \( x \), we get:
[tex]\[ x = 0 \][/tex]
Hence, the zero of the function \( y = x^4 \) is at \( x = 0 \).
2. Understanding the Transformation:
The given transformed function is \( y = (x + 4)^4 \). This transformation involves \( (x + 4) \). When we add a constant inside the function, it results in a horizontal shift. Specifically, adding a positive constant \( +4 \) inside the parentheses shifts the graph to the left by that number of units.
3. Determining the New Zero:
To find the new zero, we set the transformed function to zero and solve for \( x \):
[tex]\[ (x + 4)^4 = 0 \][/tex]
Solving for \( x \), we get:
[tex]\[ x + 4 = 0 \][/tex]
[tex]\[ x = -4 \][/tex]
Therefore, the zero of the transformed function \( y = (x + 4)^4 \) is at \( x = -4 \).
4. Comparing the Zero of the Parent and Transformed Functions:
- The original zero was at \( x = 0 \).
- The new zero is at \( x = -4 \), which means the zero has been shifted 4 units to the left from the original position.
Therefore, the correct answer is:
C. The zero of the function is shifted 4 units to the left.
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.